PROMOTIONAL STRATEGIES IN POST-COVID 19 PANDEMIC SPORTS DEVELOPMENT: A SYSTEMATIC LITERATURE REVIEW - Saputra, Danny Eka Wahyu; Suherman, Wawan Sundawan; Nugroho, Sigit; Ambardini, Rachmah Laksmi; Asmawati, Puji (MEDIKORA, 2023)
This literature review study aims to determine promotion strategies in sports development after the Covid-19 pandemic: A systematic literature review. The technique used in this research is library research. Systematic literature search on promotional strategies in post-Covid 19 sports development: A systematic literature search was conducted in Sage, Scopus, Google Scholar, and Researchgate databases. Literature analysis used a systematic literature review method. A total of three articles were selected for review. The results of the review of the articles related to processes of participation and empowerment, with sports promotion strategies taking control over what determines the health and well-being of individuals; The holistic approach has proven successful. As a result, the sports development strategy can be realized as a step towards improving the sports lifestyle of individuals. Literature analysis used a systematic literature review method. A total of three articles were selected for review. The results of the review of the articles related to processes of participation and empowerment, with sports promotion strategies taking control over what determines the health and well-being of individuals; The holistic approach has proven successful. As a result, the sports development strategy can be realized as a step towards improving the sports lifestyle of individuals. Literature analysis used a systematic literature review method. A total of three articles were selected for review. The results of the review of the articles related to processes of participation and empowerment, with sports promotion strategies taking control over what determines the health and well-being of individuals; The holistic approach has proven successful. As a result, the sports development strategy can be realized as a step towards improving the sports lifestyle of individuals.